(untitled) (ENTRENOVA - ENTerprise REsearch InNOVAtion Journal, 2017)
The business environment that is characterized by the dynamics of change has had a significant impact in the development of scientific thinking in the field of management from the beginning of the nineteenth century until today. In the 1950s, modern theories and management concepts were developed as a response to the demands of a new business environment. That particular feature, as well as the way in which its influence is accepted, enables them a potential application and importance even in a modern business environment. But, on the other hand, there are great differences between the environment in the world of the 1950s, when modern management theory appear, and the world and the environments that today are. Globalization, internationalization, virtual economy, and smart cities are just some of the features that are changing the contemporary environment and the world we live in, and which have a significant impact on the need for change and adaptation of traditional theories in business and management. The aim of the paper is to highlight the need for developing new theories and management concepts according to the problems that mangement and managers face today as the first as well as modern management theory has not been developed in accordance with today’s business and general environment. This work is licensed under a Creative Commons Attribution-NonCommercial 4.0 International License.